Oleoylethanolamide supplementation on cardiometabolic health: a systematic review and meta-analysis of randomized controlled trials - Bahari, Hossein; Jazinaki, Mostafa Shahraki; Aghakhani, Ladan; Hatami, Alireza; Rahnama, Iman; Malekahmadi, Mahsa (Frontiers in Nutrition, 2025)
BackgroundOleoylethanolamide (OEA) is a naturally occurring lipid that has been studied for its potential role in weight management and metabolic health. Through comprehensive meta-analysis, we aim to clarify the potential benefits of OEA in improving inflammation, oxidative stress, and metabolic parameters.MethodsTo identify relevant randomized controlled trials (RCTs), a comprehensive search was conducted using Google Scholar and four databases: PubMed, Embase, Scopus, and Web of Science, up to November 2024. Eligible trials were detected by screening, and related data were extracted, respectively. Pooled effect sizes were calculated using meta-analyses and expressed as standard mean difference (SMD) with a 95% confidence interval (CI).ResultsTen trials (with 11 treatment arms) were eligible for inclusion in this review. Meta-analysis revealed that OEA supplementation led to a significant improvement in C-reactive protein (CRP), tumor necrosis factor-α (TNF-α), total antioxidant capacity (TAC), malondialdehyde (MDA), body weight, body mass index (BMI), waist circumference (WC), fat mass (FM), body fat percentage (BFP), triglycerides (TG), fasting blood glucose (FBG), insulin, and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) levels. However, no significant changes were observed in interleukin 6 (IL-6), fat-free mass (FFM), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and hemoglobin A1C (HbA1c) following OEA intake.ConclusionSupplementation with OEA may help improve glycemic control, weight loss, waist circumference, fat mass, fat percentage, inflammation, and oxidative stress. However, further research is needed to establish definitive conclusions regarding its efficacy and long-term benefits.